Cert Prep: Unity Certified Associate Game Developer Animation and Cinematics. - Thorn, Alan (linkedin.com, 2021)
Bring characters and objects to life with Unity. Learn how to work with the game engine’s animation features as you prepare for the Unity Certified Associate: Game Developer exam.